2000
DOI: 10.18388/abp.2000_3979
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of membrane skeletal proteins with membrane lipid domain.

Abstract: The object of this paper is to review briefly the studies on the interaction of red blood cell membrane skeletal proteins and their non-erythroid analogues with lipids in model systems as well as in natural membranes. An important question to be addressed is the physiological significance and possible regulatory molecular mechanisms in which these interactions are engaged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 86 publications
0
10
0
Order By: Relevance
“…The organization of the plasma membrane in lipid domains affects its mechanical properties and the way it interacts with the underlying membrane skeleton (13). This interaction is believed to be critically important in the cochlear outer hair cell (OHC), one of the two types of sensory cells of the mammalian hearing organ.…”
Section: Introductionmentioning
confidence: 99%
“…The organization of the plasma membrane in lipid domains affects its mechanical properties and the way it interacts with the underlying membrane skeleton (13). This interaction is believed to be critically important in the cochlear outer hair cell (OHC), one of the two types of sensory cells of the mammalian hearing organ.…”
Section: Introductionmentioning
confidence: 99%
“…via spectrin's direct binding of phospholipids. There were many early indications that erythrocyte spectrin binds lipids in natural membranes (for a review see Sikorski et al, 2000;Grzybek et al, 2006). We found that non-erythroid spectrin (fodrin), similarly to erythroid spectrin, is able to bind aminophospholipids and also anionic phospholipids, with a reportedly even greater affinity Sikorski, 1995, 2002;Diakowski et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The structure of this domain was recently resolved by Ipsaro et al (2009). In various experimental studies ZU5 has been shown to form a novel type of protein-protein interaction interface probably involved in binding of spectrins (Sikorski et al, 2000;Zhang et al, 2004). Here specifically, the co-localization near the cell membrane allows high affinity binding of ZU5 to signal transduction proteins (Ipsaro et al, 2009).…”
Section: Resultsmentioning
confidence: 99%